Chromium Stress Tolerance of a C4 (Zea mays L.) and C3 (Vigna radiata L.) Plants Primed with UV and Gamma-Treated Bacillus subtilis - Qasim Shahzad; Saqib Mahmood; Sadia Javed; Tariq Mushtaq (Microorganisms, 2021)
Chromium stress is one of the deleterious abiotic factors that reduce crop production. Two anatomically different crops (C3 and C4) were compared for their chromium (0 and 50 ppm) tolerance and responses towards Bacillus subtilis (B. subtilis). Strains of B. subtilis were exposed to UV (30–210 min) and gamma irradiation (1–4 KGy), and the best mutants were selected on petri plates containing selective markers. Maize and mungbean were supplied with selected strains or the parent strain in rooting medium, along with a nutrient broth. A completely randomized design (five replicates) was adopted using nutrient broth as a control. Stress negatively affected plants grown without strains. Mungbean was more sensitive towards stress and treatments, maize had better root and shoot fresh weights, root and shoot lengths, proline levels, and MDA and GR activity. All strains of B. subtilis (parent, γ-irradiated and UV-irradiated) enhanced proline, total soluble protein, chlorophyll a, a + b and a/b levels, with negligible effects upon antioxidant enzymes. Irradiated strains proved their superiority to the parent strain, with reductions in H2O2 and MDA content. With comparable benefits, γ and UV irradiation may be adopted in future based upon technical availability.